Deconstructing the Kiai and Santri Relationship: A Critical Review of Power and Cultural Dynamics - Achmadin, Balya Ziaulhaq; Asrori, Mohammad; Barizi, Ahmad; Amrullah, Abdul Malik Karim; Nafis, Muhammad Muntahibun (el Harakah: Jurnal Budaya Islam, 2024)
This study aims to reveal the dynamics of the relationship between Kiai and santri in traditional pesantren. This research deconstructs the relationship between Kiai and Santri in the Indonesian socio-cultural context. Through a critical approach, this study examines the dynamics of power and cultural influences that color the relationship. By analyzing various sources, this study reveals the complexity of the Kiai and Santri relationship that goes beyond the traditional teacher-student relationship. The results show that the relationship between Kiai and santri in traditional pesantren is built on the basis of strong religious and cultural values. Kiai holds a central role as a spiritual leader and teacher, while santri place themselves as obedient and respectful students. This relationship is characterized by a clear hierarchy, where Kiai has great authority and influence over santri. However, the dynamics of this relationship do not always run smoothly. There are potential conflicts that arise due to differences in interpretation of religious values, differences in socio-economic backgrounds, and the influence of changing times. Kiai are required to be able to maintain a balance between maintaining traditional values and adjusting to the demands of the times and their relevance to social and political changes affecting the relationship between Kiai and Santri Penelitian ini bertujuan untuk mengungkap dinamika hubungan antara Kiai dan santri di pesantren tradisional. Penelitian ini mendekonstruksi hubungan Kiai dan Santri dalam konteks sosial-kultural Indonesia. Melalui pendekatan kritis, penelitian ini mengkaji dinamika kekuasaan dan pengaruh budaya yang mewarnai hubungan tersebut. Dengan menganalisis berbagai sumber, penelitian ini mengungkap kompleksitas hubungan Kiai dan Santri yang melampaui relasi guru-murid tradisional. Hasil penelitian menunjukkan bahwa hubungan Kiai dan santri di pesantren tradisional dibangun atas dasar nilai-nilai religius dan kultural yang kuat. Kiai memegang peran sentral sebagai pemimpin spiritual dan guru, sementara santri menempatkan diri sebagai murid yang patuh dan hormat. Hubungan ini ditandai dengan hierarki yang jelas, di mana Kiai memiliki otoritas dan pengaruh yang besar terhadap santri. Namun, dinamika hubungan ini tidak selalu berjalan mulus. Terdapat potensi konflik yang muncul akibat perbedaan interpretasi nilai-nilai agama, perbedaan latar belakang sosial-ekonomi, dan pengaruh perubahan zaman. Kiai dituntut untuk mampu menjaga keseimbangan antara mempertahankan nilai-nilai tradisional dan menyesuaikan diri dengan tuntutan zaman serta relevansinya dengan perubahan sosial dan politik memengaruhi hubungan Kiai dan Santri